2012
DOI: 10.3758/s13415-012-0122-x
|View full text |Cite
|
Sign up to set email alerts
|

High temporal discounters overvalue immediate rewards rather than undervalue future rewards: An event-related brain potential study

Abstract: Impulsivity is characterized in part by heightened sensitivity to immediate relative to future rewards. Although previous research has suggested that "high discounters" in intertemporal choice tasks tend to prefer immediate over future rewards because they devalue the latter, it remains possible that they instead overvalue immediate rewards. To investigate this question, we recorded the reward positivity, a component of the event-related brain potential (ERP) associated with reward processing, with participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
46
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 45 publications
(59 reference statements)
6
46
2
Order By: Relevance
“…Consistent with this finding, we found that the procrastination group showed an overall larger P2 during the time delay and reward processing. Together with previous findings about high discounters with a larger reward positivity (250-300 ms post-stimulus; Cherniawsky & Holroyd, 2013), our findings of the P2 effect may reflect the overall higher sensitivity to time delay and reward information, which may be due to a higher level of impulsivity among high procrastinators.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Consistent with this finding, we found that the procrastination group showed an overall larger P2 during the time delay and reward processing. Together with previous findings about high discounters with a larger reward positivity (250-300 ms post-stimulus; Cherniawsky & Holroyd, 2013), our findings of the P2 effect may reflect the overall higher sensitivity to time delay and reward information, which may be due to a higher level of impulsivity among high procrastinators.…”
Section: Discussionsupporting
confidence: 58%
“…In the past decade, several brain-imaging studies using intertemporal choice tasks have revealed that the limbic system (including the ventral striatum) and the executive function system (including the lateral and medial prefrontal cortex) are involved in intertemporal decision making (Albrecht, Volz, Sutter, Laibson, & von Cramon, 2011;Bickel, Pitcock, Yi, & Angtuaco, 2009;Figner et al, 2010;Kable & Glimcher, 2007;Takahashi et al, 2009). In contrast, despite the high temporal resolution of the ERP technique, to our knowledge there have been few attempts to combine it with intertemporal choice tasks (Cherniawsky & Holroyd, 2013;Li et al, 2012;Oswald & Sailer, 2013). However, one recent work has found that the P2 reflects the temporal distance effect (He, Huang, Yuan, & Chen, 2012).…”
Section: Introductionmentioning
confidence: 76%
“…Accordingly, we were only able to investigate the relationship between delay-discounting responses and neural activity to immediate-reward stimuli. Future research may wish to vary whether rewards are delivered immediately or following a delay, as in previous research (Cherniawsky & Holroyd, 2013). Similarly, while the delay-discounting task in the present study employed hypothetical monetary rewards, the time-estimation reward task employed real monetary rewards.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have revealed that it actually reflects reward-related dopaminergic activity and should be re-interpreted as a larger positivity in the positive feedback condition rather than a negative component in the negative feedback condition (Foti et al, 2011; Walsh and Anderson, 2012; Proudfit, 2015). In the delay discounting task, Cherniawsky and Holroyd (2013) found that a larger RewP elicited by immediate compared to delayed rewards indicates a stronger preference for impulsive choices (Onoda et al, 2010; Mason et al, 2012). In addition, the RewP might also reflect individual differences in intolerance of uncertainty, since this component is sensitive to the uncertainty of an outcome feedback (Hirsh and Inzlicht, 2008; Nelson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%